Headache attributed to SARS-CoV-2 infection, vaccination and the impact on primary headache disorders of the COVID-19 pandemic: A comprehensive review - Caronna, Edoardo; van den Hoek, Thomas C.; Bolay, Hayrunnisa; Garcia-Azorin, David; Gago-Veiga, Ana Beatriz; Valeriani, Massimiliano; Takizawa, Tsubasa; Meßlinger, Karl; Shapiro, Robert E.; Goadsby, Peter J.; Ashina, Messoud; Tassorelli, Cristina; et al. (Cephalalgia, 2023)
OBJECTIVE: The objective is to summarize the knowledge on the epidemiology, pathophysiology and management of secondary headache attributed to SARS-CoV-2 infection and vaccination; as well as to delineate their impact on primary headache disorders. METHODS: This is a narrative review of the literature regarding primary and secondary headache disorders in the setting of COVID-19 pandemic. We conducted a literature search in 2022 on PubMed, with the keywords "COVID 19" or "vaccine" and "headache" to assess the appropriateness of all published articles for their inclusion in the review. RESULTS: Headache is a common and sometimes difficult-to-treat symptom of both the acute and post-acute phase of SARS-CoV-2 infection. Different pathophysiological mechanisms may be involved, with the trigeminovascular system as a plausible target. Specific evidence-based effective therapeutic options are lacking at present. Headache attributed to SARS-CoV-2 vaccinations is also common, its pathophysiology being unclear. People with primary headache disorders experience headache in the acute phase of COVID-19 and after vaccination more commonly than the general population. Pandemic measures, forcing lifestyle changes, seemed to have had a positive impact on migraine, and changes in headache care (telemedicine) have been effectively introduced. CONCLUSIONS: The ongoing COVID-19 pandemic is a global challenge, having an impact on the development of secondary headaches, both in people with or without primary headaches. This has created opportunities to better understand and treat headache and to potentiate strategies to manage patients and ensure care.
CRIS-Team Scopus Importer:2023-01-13
Keywords: COVID-19; Headache; migraine; SARS-CoV-2; telemedicine; vaccine